The role of Kazakhstan in the Eurasian economic union - RUSLAN ZHAKUPOV (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The study’s overarching goal is to examine Kazakhstan’s efforts to join international organizations. Using a multi-pronged foreign policy, Kazakhstan is preparing to play a significant role in a wide variety of international organizations, including the Eurasian Economic Union (EEU).Method: The study includes a comprehensive literature review of research on Kazakhstan’s participation in the Eurasian Economic Union and its relations with the other member states.Findings: The findings prove beyond a reasonable doubt that Kazakhstan was an instrumental player in the establishment and growth of the EEU. The potential benefits of continuing to implement this initiative are substantial, and it represents one of the country’s top policy priorities. Moreover, a considerable part of it has already been translated into reality.Implications/Novel Contribution: The article offers new insight by discussing the opportunities for Uzbekistan and Tajikistan to join the EEU alongside the foreign policy interests of Kazakhstan within the organization. Few studies have been done on this topic so far.